Development of Alternative Energy Transition Scenarios for Electricity Utility Companies in 2045 Using the Scenario Planning Method: - Imtihan, Najahul; Rendroyoko, Ignatius (International Journal of Industrial Engineering and Engineering Management, 2025)
In implementing the energy transition, electricity utility companies must be able to carry out future planning to replace electricity infrastructure from a fossil energy-based generation system to clean energy generation and new renewable energy (NRE) to achieve Net Zero Emission (NZE) conditions by 2060. Term planning. What has often been done so far is to use forecasting methods, which are made by utilizing historical databases and using many assumptions about economic, social, and environmental conditions, as well as other factors that are easily changed and close to uncertainty. Therefore, planning methods must consider possible changes and uncertainties with several possible scenarios. Scenario planning is planning with a strategic approach that focuses on the process, involving finding optimal strategies for several scenarios that can occur, and this method helps deal with uncertainty. This paper explores the development of alternative scenarios that may occur in 2045, using scenario planning to help electricity utility companies capture opportunities and offset threats. It focuses on formulating broad and innovative strategies for the energy transition in the electricity business.